Characterization of the ExoS/ChvI two-component system in Sinorhizobium meliloti, a nitrogen fixing symbiont of Medicago truncatula - Sabio, Erich (ProQuest Dissertations & Theses, 2009)
Sinorhizobium meliloti forms a symbiosis with Medicago truncatula in which the bacteria provide fixed nitrogen to the plant in exchange for carbon compounds for energy. Bacteria use two-component systems for signal transduction. Two-component systems are composed of a sensor kinase that interacts with an external signal and a response regulator that binds to DNA to regulate gene expression. In S. meliloti, the ExoS/ChvI two-component system is critical for symbiosis, free-living viability, biofilm formation, and motility. This research addresses three aspects of ExoS/ChvI function. First, I characterized the relationship between ExoS/ChvI and ExoR, a putative negative regulator of ExoS/ChvI. Second, we explored whether ropB1 and smc01580, two putative target genes of ExoS/ChvI, are indeed regulated by ExoS/ChvI. Third, to identify direct transcriptional target genes of ExoS/ChvI, I tested whether ChvI binds to specific promoters. Since ExoS/ChvI orthologs and some of their effectors have been shown to be virulence factors in pathogenic bacteria related to S. meliloti, this characterization of ExoS/ChvI signaling in S. meliloti provides insight into the mechanisms involved in both mutualistic and parasitic symbioses.